Development of agent-oriented software components to retrieve the marketing information from the web - Cherednichenko, Olga Yurevna; Melnyk, K. V.; Kirkin, Stanislav Vasylevich; Sokolov, Dmitry Vitalevich; Matveev, Alexander Nikolaevich (НТУ "ХПІ", 2018)
The article is devoted to researching the processes of extracting marketing information from the Web space. Conclusions are drawn on the need to introduce an information marketing system into modern business activities. A decision has been taken to develop software for the collection and analysis of marketing information. Identified and analyzed the main problems of collecting marketing information in the Web space. External systems for extracting and processing marketing information from the Web space were considered. During the analysis of the subject area, functional and non-functional requirements for the software being developed were formulated. Requirements for the selection of technologies for the development of an information system were defined. The analysis of software development technologies is carried out and the approach to the development of a software component is chosen. Such approaches to software development as: object-oriented programming, service-oriented architecture, component-oriented programming, agent-oriented programming were analyzed. A decision has been made to use the agent three-tier architecture in software development. The most commonly used programming languages in programming systems were: Java, KIF, KQML, AgentSpeak, April, TeleScript, Tcl / Tk, Oz. Analyzed such popular agent platforms and their functions as: JADE, Cougaar, ZEUS, Jason. For the development of software, the JADE platform was chosen, its classes, methods and interfaces were examined. The advantages and peculiarities of the SOLID principle are analyzed. In detail, the levels of the CLEAN architecture are examined. And also explained the possibilities of software implementation of this architecture. A software architecture was developed for the data collection system. In accordance with the requirements, a selection of software development tools has been made. It was decided to use the programming language Java, Spring Framework, GoF design pattern, the template Dependency Injection, SOLID and CLEAN architectural principles. A software component was developed for marketing information gathering systems, which allows to optimize this process. The limitations and ways to improve the software system are analyzed.

Статтю присвячено питанням дослідження процесів вилучення маркетингової інформації з Web-простору. Зроблено висновки про необхідність введення інформаційної маркетингової системи в сучасну підприємницьку діяльність. Прийнято рішення про розробку програмного забезпечення для збору та аналізу маркетингової інформації. Виявлено та проаналізовано основні проблеми збору маркетингової інформації у Web-просторі. Були розглянуті зовнішні системи по вилученню та обробці маркетингової інформації з Web-простору. В ході аналізу предметної області були сформульовані функціональні і нефункціональні вимоги до розроблюємого програмного забезпечення. Були визначені вимоги до вибору технологій для розробки інформаційної системи. Проведено аналіз технологій розробки програмного забезпечення та обрано підхід до розробки програмного компонента. Були проаналізовані такі підходи до розробки програмного забезпечення як: об’єктно-орієнтоване програмування, сервіс-орієнтована архітектура, компонентно-орієнтоване програмування, агентно-орієнтоване програмування. Прийнято рішення про використання агентної трирівневої архітектури в розробці програмного забезпечення. Були розглянуті найбільш часто використовувані в агентних системах мови програмування: Java, KIF, KQML, AgentSpeak, April, TeleScript, Tcl/Tk, Oz. Проаналізовано такі популярні агентні платформи і їх функції як: JADE, Cougaar, ZEUS, Jason. Для розробки програмного забезпечення була обрана платформа JADE, розглянуті її класи, методи і інтерфейси. Проаналізовано переваги та особливості принципу SOLID. В деталях розглянуті рівні архітектури CLEAN. А також зроблені пояснення можливостей програмної реалізації цієї архітектури. Була розроблена програмна архітектура для системи зі збору даних. Відповідно до вимог зроблений вибір інструментів розробки програмного продукту. Прийнято рішення про використання мови програмування Java, Spring Framework, GoF патерну проектування, шаблону Dependency Injection, SOLID і CLEAN архітектурних принципів. Був розроблений програмний компонент для систем збору маркетингової інформації, що дозволяє оптимізувати цей процес. Проаналізовано обмеження і шляхи поліпшення програмної системи
Розробка агентно-орієнтованих компонентів програмного забезпечення для вилучення маркетингової інформації з web
Keywords: architecture; JADE; marketing data; CLEAN; agent; program system; Java; архітектура; маркетингові дані; агент; програмна система